Pitting growth rate on Alloy 800 in chloride solutions containing thiosulphate: image analysis assessment. (3rd April 2018) - Wang, Zeqing; Wang, Jianqiu; Behnamian, Yashar; Gao, Zhiming; Wang, Jihui; Xia, Da-Hai
ABSTRACT: The growth rate of pits formed on Alloy 800 in chloride solutions containing various thiosulphate concentrations was assessed by potentiostatic polarisation, in situ corrosion image observation, and image analysis. The pitting growth rate was a function of solution chemistry: in chloride solution pits were small but numerous, in chloride + thiosulphate solution, the pits were large. Competitive adsorption on Alloy 800 of chloride and thiosulphate ions affected the pitting potential and therefore the pitting growth rate on the metal. The reduction of thiosulphate to elemental sulphur accelerated the pitting growth rate in chloride + thiosulphate solutions.